Desenvolvimento de um modelo animal de depressão para estudo de fármacos antidepressivos de ação rápida - Torres, Carina Ioná de Oliveira (2023)
Major Depressive Disorder (MDD) is characterized as one of the most prevalent and disabling mental disorders in the world. The pharmacological treatment of depression has important limitations, such as low efficacy, several side effects and the delay in the onset of therapeutic effects, thus contributing to poor adherence to pharmacotherapy. In this context, the identification of fast-acting antidepressant drugs can contribute to improving the life quality of depressive patients. Given the ethical and practical limitations linked to clinical studies, animal models are useful tools to investigate innovative drugs. However, there are not still available animal models of depression sensitive to detect fast-acting antidepressants, and the development of an animal model with this profile could represent a substantial advance in the investigation of biological bases and treatment of MDD. To this aim, the present project evaluated chronic exposure to oral glucocorticoids as an animal model to identify fast-acting antidepressants. Male Swiss mice were submitted to pilot tests to select the glucocorticoid to be used in sequence and the appropriate experimental conditions for carrying out the behavioral tests. In a second step, mice were orally exposed for at least 28 uninterrupted days to mineral water (control) or hydrocortisone dissolved in water (0.1 and 0.033 mg/ml). Throughout the exposure period, Sucrose Preference Test, Campo Aberto, Murble Buring, Teste de Respingo, Tail Suspension, Object Recognition, Social Interaction and Forced Swimming Test were performed to investigate behaviors related to depression, anxiety, memory and locomotion. On the 21st day, mice treated with hydrocortisone were divided into groups that received, intraperitoneally, ketamine (10 and 100 mg/kg) or vehicle one single administration. Our findings suggested that hydrocortisone 0.1 mg/ml induced depressionand anxiety-related behaviors, hyperlocomotion, and significant weight loss and deaths. At a lower dose (0.033 mg/kg), hydrocortisone evoked anxiogenic effects in the first days of exposure, while anhedonic behavior appeared after 2 weeks oral glucocorticoid ingestion. Despite the small sample size, acute treatment with ketamine (depending on the dose), in turn, tended to attenuate hydrocortisone (0.033 mg/ml) -induced anhedonia, anxiogenic-like and hyperlocomotor effects, especially after 4 days of administration. Finally, the data presented herein indicate that the proposed model of repeated exposure to oral hydrocortisone was able to mimic the behavioral (symptomatic) changes presented by patients with MDD, thus presenting good face validity.